Host Neuro- Immuno-Endocrine Responses In Periodontal Disease - Rettori, Elisa; De Laurentiis, Andrea; Les Dees, W.; Endruhn, Axel; Rettori, Valeria (Current Pharmaceutical Design, 2014)
Periodontitis is a chronic inflammatory complex disease caused by microorganisms. It may be influenced by diverse systemic disorders, environmental, genetic and socio-psychological factors with the ability to alter the balance of the host neuro-immunoendocrine responses. It is characterized by the progressive destruction of the tooth supporting apparatus leading to tooth loss, with possible impact on general health. Starting with a brief description of the periodontium, etiopathogenesis, repair processes and several physiological mechanisms and their disarray on periodontium response to bacterial challenge. Following, the negative effects of stress on the disease and some remarks on the recently discovered effects of oxytocin that modulate stress response and its role in individual coping mechanisms to stress. We also focus on the participation of components and functions of endocannabinoid system with anti-inflammatory actions on gingiva. Finally, a discussion that may link between diabetes, cardiovascular diseases, stroke and metabolic syndrome associated with periodontal disease; all of them sharing a common denominator that is inflammation and oxidative stress.
Keywords: stress